Dissertações e Teses - Stigger, Helena; Santos, Hilário dos; Cunha, Karen; BomFim, Leonardo; Freitas, Almir Penha de; Dalcim, Fabiano; Chaves, Carolina; Freitas, Fernanda Lopes de (Revista FAMECOS, 2012)
.